Dynamics of psychological microclimate indices in student groups of medical higher education institutions and their role in development of psychosomatic disorders in students - Zemlyakova, T.D.; Antonova, O.V. (Актуальні проблеми транспортної медицини, 2017)
The article presents the dynamics of the psychological microclimate indices in student groups of medical faculties in the medical higher school (2009-2014-2016 years) and their role in development of psychosomatic disorders in students with underlying predisposition to stressful situations. 709 students have participated in studies, 1001 questionnaires have been processed. The obtained data allowed us to estimate the level of psychological compatibility of students of both faculties (the degree of their “ friendliness”), the authority of group presidents (formal leaders) and true leaders, the number of outsiders (students who have psychological compatibility with the members of the group of less than 50%), as well as the number of conflicts, including multiple. The research results have been used for recreational and corrective method, representing the methodological guidelines “Autogenic training as an active method of increasing the psychological working capacity of students and lecturers.”.